Organization theory : modern, symbolic, and postmodern perspectives - Hatch, Mary Jo (Oxford University Press, 1997)
"Organization Theory offers a clear and comprehensive introduction to the study of organizations and provides an even-handed appreciation of the different perspectives that have contributed to our knowledge of organizations." "In order to aid learning the text provides many diagrammatical and conceptual models and each chapter includes a summary, a list of key terms, and pointers to further reading. Organization Theory is essential reading for all courses on organization theory and organizational analysis at undergraduate and postgraduate levels. It will also be useful for courses on organizational behavior, the sociology of work, and human resource management."--Jacket.